A Multimodal Approach to Quantify Chondrocyte Viability for Airway Tissue Engineering. (25th May 2022) - Chan, Coreena; Liu, Lumei; Dharmadhikari, Sayali; Shontz, Kimberly M.; Tan, Zheng Hong; Bergman, Maxwell; Shaffer, Terri; Tram, Nguyen K.; Breuer, Christopher K.; Stacy, Mitchel R.; Chiang, Tendy
Abstract : Objectives/Hypothesis: Partially decellularized tracheal scaffolds have emerged as a potential solution for long‐segment tracheal defects. These grafts have exhibited regenerative capacity and the preservation of native mechanical properties resulting from the elimination of all highly immunogenic cell types while sparing weakly immunogenic cartilage. With partial decellularization, new considerations must be made about the viability of preserved chondrocytes. In this study, we propose a multimodal approach for quantifying chondrocyte viability for airway tissue engineering. Methods: Tracheal segments (5 mm) were harvested from C57BL/6 mice, and immediately stored in phosphate‐buffered saline at −20°C (PBS‐20) or biobanked via cryopreservation. Stored and control (fresh) tracheal grafts were implanted as syngeneic tracheal grafts (STG) for 3 months. STG was scanned with micro‐computed tomography (μCT) in vivo. STG subjected to different conditions (fresh, PBS‐20, or biobanked) were characterized with live/dead assay, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL), and von Kossa staining. Results: Live/dead assay detected higher chondrocyte viability in biobanked conditions compared to PBS‐20. TUNEL staining indicated that storage conditions did not alter the proportion of apoptotic cells. Biobanking exhibited a lower calcification area than PBS‐20 in 3‐month post‐implanted grafts. Higher radiographic density (Hounsfield units) measured by μCT correlated with more calcification within the tracheal cartilage. Conclusions: We propose a strategy to assess chondrocyte viability that integrates with vivo imaging and histologic techniques, leveraging their respective strengths and weaknesses. These techniques will support the rational design of partially decellularized tracheal scaffolds. Level of Evidence: N/A Laryngoscope, 133:512–520, 2023